Pengaruh Locus Of Control terhadap Prestasi Belajar Matematika - Yulia Septiani (Universitas Indraprasta PGRI, 2016)
The research is aimed to analyze the impacts of locus of control on mathematical learning achievement. The benefits of this research are to analyze the impacts of locus of control on mathematical learning achievement. The method used in this research is expose facto with comparation analysis. The research was conducted on the students X grade at SMK Negeri 1 Cikarang Barat in West Cikarang. Sample size is 67 taken from 207 affordable population.The instrument used is questionnaire and they have been empirically validated. Analysis technique for the data is descriptive and inferensial by using test after the data fulfill normality test and homogenity test. Based on the research, it can be concluded, there are significant impacts of internal locus of control on mathematical learning achievement of students X grade SMK Negeri 1 Cikarang Barat in West Cikarang, Bekasi West of Java. It can be proved by count > table.